How the cultural sector can become a ‘global good’ for sustainable development (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
In September 2022, UNESCO organised a conference called Mondiacult in Mexico, to explore the relationships between cultural policy and sustainable development, looking towards the next sustainable development programme that will replace Agenda 2030 and the SDGs in 2030. How can the cultural sector – particularly museums, galleries, libraries and archives – relate to the Agenda and the SDGs?